RELATIONSHIP OF PERSONAL HYGIENE AND SANITARY HYGIENE CONDITIONS WITH SOIL TRANSMITTED HELMINTS (STH) WORM INFECTIONS IN ELEMENTARY SCHOOL CHILDREN - Andiyana Nur Wulan (UNIVERSITAS BHAMADA SLAWI, 2023)
Helminths can attack all age groups and genders. Helminths can cause a decrease in health conditions, intelligence, productivity, and the quality of human resources, resulting in economic losses due to loss of carbohydrates, protein, blood, and can reduce body resistance so that it is easy to get other diseases. This research uses quantitative research type. The population in this study were elementary school children in SDN Dukuh Kupang V Surabaya with the number of 50 children. This study uses a sampling technique in the form of total sampling. The data collected in this study include primary data and secondary data where the primary data is in the form of STH worm infection data obtained from the direct method of examination of respondents' feces. Secondary data in the form of hygiene and sanitation obtained through questionnaires. The data that has been obtained is then analyzed and looked for correlation using the product moment test. Based on the results of the study and after a series of analyzes and discussion of the results of the examination of the 50 samples examined, 32% (16 people) had positive results while the rest were negative, it was concluded that there was a significant relationship between environmental sanitation and personal hygiene (hand washing habits, nail hygiene, and use of footwear) with Soil Transmitted Helminths (STH) infection in primary school children. So it is expected to always wash hands with water and soap so that it is more effective in removing dirt and dust mechanically from the skin surface and significantly reduces the number of disease-causing microorganisms such as viruses, bacteria, and other parasites on both hands on the skin surface, nails, and fingers.